Single-phase cuprite thin films prepared by a one-step low-vacuum thermal oxidation technique - Du, Wenhan (2021)
Cu₂O thin film solar cells have attracted the interest of many researchers owing to their non-toxic and earth-abundant properties. High-quality pure-phase Cu₂O thin films were prepared by using a simple low-vacuum thermal annealing technique. The growth temperatures of the Cu₂O thin films were varied from 400 to 1000°C. X-ray diffraction (XRD) and scanning electron microscopy were used to characterise the structural and morphological changes of the thin films. The XRD results suggested that all the films were pure-phase Cu₂O; thus, no second-phase CuO was observed. The detailed evolution of the surface morphology was investigated. The electron dispersion spectrum (EDS) results show that the atomic ratio of Cu and O were changed with the annealing temperature, the ratio change from around 2: 1 to 1.84: 1 with the turning temperature of 800°C, indicating copper vacancy formed during annealing temperature higher than 800°C. EDS results well matched the d-spacing changes of the XRD results.